SAT0291 Clinical Relevance of FGF-23 in Dialysis Tunisian Patients. (9th June 2015) - Slouma, M.; Sahli, H.; Rekik, S.; Laadhar, L.; Smaoui, W.; Boussaid, S.; Bahlous, A.; Cheour, E.; Ben Moussa, F.; Sallami, M.; Elleuch, M.
Abstract : Background: Fibroblast growth factor-23 (FGF23) is a bone-derived hormone. The association between FGF-23 levels and clinical outcome in hemodialysis patients suggests that FGF-23 can be considered as a cardiovascular risk in this population, Moreover, relationship between FGF-23 and osteoporosis remains unclear in dialysis patients. Objectives: The aim of the study was to demonstrate the association between FGF-23 levels with either osteoporosis and cardiovascular risk factors in hemodialysis patients. Methods: We conducted a transversal study over a period of 4 years [2009-2012] including 80 patients under hemodialysis therapy over one year period. Blood samples were drawn before hemodialysis session from patients. We measured calcium, phosphate, 25 OH-vitamin D and fibroblast growth factor (FGF23). Bone mass density (BMD) was measured by dual energy X-ray absorptiometry (DXA) at the lumbar spine and total hip. Lumbar spine X-rays were used to diagnose vascular calcification. All statistical analysis were performed using the Windows SPSS 19 package. Results: Eighty patients were included: 51 male and 29 female. The mean age was 53.27 years [20; 89]. The mean age of onset of hemodialysis was 50.42±14.49 years. The mean body mass index (BMI) was 25.91±4.86 kg/m 2 and the mean weight was 68.16±13.36 kg. Diabetes, hypertension and dyslipidemia were observed respectively in 45%, 66.3% and 15% of cases. Serum calcium and phosphorus levels were respectively 2.06±0.39 mmol/L and 1.83±0.57 mmol/L. The average rates of parathyroid hormone (PTH), vitamin D and FGF23 were respectively 422.60±382.8 pg/mL 15.92±11.39 ng/mL, and 248.96±221.87 pg/mL. Osteoporosis affected the hip in 20% of cases and the spine in 9% whereas osteopenia was observed in 44% of cases in the hip and 33% of cases in the spine lumbar. Vascular calcifications (CV) were found in 31.11% of cases. Negative correlation was observed between FGF23 and vitamin D (r: -0.245, p: 0.027). Patients with dyslipidemia had higher FGF23 levels than patients without dyslipidemia (239.28 pg/mL vs 123.19pg/mL). No correlation was found between FGF23 and following parameters: calcium and phosphorus levels, PTH levels, BMI and weight. FGF levels 23 tend to be higher in hemodialysis with CV but this difference was not significant (275.85 pg/mL vs 195.88 pg/mL, p:0.231). Lumbar osteoporosis was associated with high concentrations of FGF23. Conclusions: Our study showed that FGF-23 levels are increased in hemodialysis patients. We demonstrate also that higher concentrations of FGF23 are associated with osteoporosis in lumbar spine. Given the association FGF23 and dyslipidemia, this factor can be considered as a cardiovascular risk in hemodialysis patients. Disclosure of Interest: None declared